Factors Influencing the Decline in Use of The Nebengers Application - Christine Cecylia Munthe; Panca Oktavia Hadi Putra (Jurnal Sistem Informasi, 2025)
Nebengers is a popular ride-sharing application that helps many users find traveling companions and reduces the use of private vehicles in several regions in Indonesia. In 2022, there has been an increase in travel requests but a decrease in trip completion; in fact, only twenty-five percent of travel requests have been completed. This research aims to analyze the factors influencing the decline in trip completion in the Nebengers application based on the user's perspective. The identification process was carried out by conducting interviews with guided questions referring to the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) Model and the Systematic Literature Review (SLR) results. Thematic analysis was used to identify factors discovered during the interviews. The results of the thematic analysis are four themes of factors that influence the use of the Nebengers application: Effort Expectancy, Facilitating Conditions, Hedonic Motivation, and Habit.